Tomographic mapping of a coastal upwelling and the associated diurnal internal tides in Hiroshima Bay, Japan. Issue 6 (15th June 2015) - Zhang, Chuanzheng; Kaneko, Arata; Zhu, Xiao‐Hua; Gohda, Noriaki
Abstract: Temperature variations caused by a typhoon were measured in the northern part of Hiroshima Bay by four coastal acoustic tomography (CAT) systems. The horizontal distributions of depth‐averaged temperature from 0 to 8 m were mapped at 10 min intervals between the 11 and 25 September 2013. The horizontal distributions of a coastal upwelling and the associated diurnal internal tides were reconstructed well by regularized inversion based on the grid segmented method, using one‐way travel time data along five successful sound transmission lines. Station‐to‐station ranges were corrected in such a way that sound speed (determined from one‐way travel time data) was equal to sound speed calculated from a couple of CTD (conductivity‐temperature‐depth) data sets on each transmission line. In addition, all station positions were adjusted to make focal points at the geographical positions of the transducers. The corrections increased the accuracy of temperature measurements to make temperature errors as small as 0.073–0.079°C. The high accuracy made it possible to map the temperature structure with a variation range of less than 0.5°C. An upwelling grew from 16 to 17 September, due to a typhoon‐derived northerly wind. The diurnal internal tide resonated with the semidiurnal external tide, which was pronounced after the upwelling decayed (18 September), around the time the spring tide occurred. The upwelling and mixing fractions were formulated. These fractions increased continuously as the upwelling grew. Complete mixing was observed during the upwelling's mature phase. Key Points: Mapping the horizontal structure of temperature by coastal acoustic tomography Coastal upwelling and the associated diurnal internal tide generated by typhoon Formulating the upwelling and mixing fractions for growing coastal upwelling